CARBON-FIBRE-REINFORCED POLYMER PARTS EFFECT ON SPACECRAFT OPTOELECTRONIC MODULE LENS SCATTERING - S. S. Kolasha; R. V. Fiodortсev; A. V. Starovoitov (Приборы и методы измерений, 2016)
Spacecraft optoelectronic modules traditionally have aluminum alloy or titanium alloy casing which substantial weight increases fuel consumption required to put them into orbit and, consequently, total cost of the project. Carbon fiber reinforced polymer based composite constructive materials is an efficient solution that allows reducing weight and dimensions of large optoelectronic modules 1,5–3 times and the coefficient of linear thermal expansion 15–20 times if compared with metals. Optical characteristic is a crucial feature of carbon-fibre-reinforced polymer that determines composite material interaction with electromagnetic emission within the optical range. This work was intended to develop a method to evaluate Carbon fiber reinforced polymer optoelectronic modules casing effect on lens scattering by computer simulation with Zemax application software package. Degrees of scattered, reflected and absorbed radiant flux effect on imaging quality are described here. The work included experimental study in order to determine bidirectional reflectance distribution function by goniometric method for LUP-0.1 carbon fabric check test pieces of EDT-69U epoxy binder with EPOFLEX-0.4 glue layer and 5056-3.5-23-A aluminium honeycomb filler. The scattered emission was registered within a hemisphere above the check test piece surface. Optical detection direction was determined with zenith (0º < θ < 90º) and azimuth (0º < φ < 180º) angles with 10° increment. The check test piece surface was proved to scatter emission within a narrow angle range (approximately 20°) with clear directivity. Carbon fiber reinforced polymers was found to feature integrated reflectance coefficient 3 to 4 times greater than special coatings do.